2014
DOI: 10.4236/oalib.1100427
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Low Grade Egyptian Manganese Ore via Hydrogen at 800℃ - 950℃

Abstract: Low grade manganese ore fine was briquetted with different amounts of molasses under different pressure was studied in this investigation. In this study, the characterizations of raw materials were studied by different methods of analyses such as X-ray and chemical analyses. The results of briquetting show that as the pressing pressure load increased both the drop damage resistance and crushing strength increased and the optimum amount of molasses added was 2% and the pressing pressure was 216.7745 MPa. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Manganese is an important raw material for the cells production, preparation of the steel, dietary additives and fine chemicals [1,2]. With the ever increasing demand for manganese resources and the depletion of high grade ores, exploitation and utilization of low-grade manganese ores becomes increasingly important [3,4].…”
Section: Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese is an important raw material for the cells production, preparation of the steel, dietary additives and fine chemicals [1,2]. With the ever increasing demand for manganese resources and the depletion of high grade ores, exploitation and utilization of low-grade manganese ores becomes increasingly important [3,4].…”
Section: Instructionmentioning
confidence: 99%
“…The increase of reduction percentage with rise of temperature may be due to the increase of number of reacting moles having excess of energy which leads to the increase of reduction rate. Also the raise of temperature leads to an increase of the rate of mass transfer of the diffusion and rat of desorption [2,15]…”
Section: Effect Of the Roasting Temperature Of Manganese Dioxide Ore On The Manganese Reduction Ratementioning
confidence: 99%
“…Metallurgical coke is the main solid carbon reductant that is used in SAF. The dependence of the process on the solid carbon use is in principle related to the thermochemistry of manganese monoxide (MnO) reduction, which is viable by carbon and not by H 2 and CO gases, as previously described. , In principle, the reduction of higher manganese oxides (MnO 2 , Mn 2 O 3 , and Mn 3 O 4 ) to MnO is possible by H 2 and CO gases . Natural gas, which is rich in methane (CH 4 ), is a more sustainable alternative reductant for metal and ferromanganese production in comparison with metallurgical coke and, therefore, there has been a significant research interest in using this reductant. ,,, However, the application of natural gas at elevated temperatures yields CO and H 2 gas mixtures and the reduction by these gases cannot proceed beyond MnO, and this has been the basis for many researchers to use natural gas for the prereduction of the ore as reviewed previously .…”
Section: Introductionmentioning
confidence: 98%
“…The reduction of MnFe 2 O 4 by hydrogen at 257-767 • C has shown that the product is a mixture of MnO and metallic Fe. Hydrogen reduction of low-grade Mn briquets by H 2 at 750 to 950 • C indicated the production to MnO phases [10,11]. Hence, reactions (1) to (3) proceed in a wide temperature range and complete reduction to MnO is possible.…”
Section: Introductionmentioning
confidence: 99%